2014
DOI: 10.1093/jpepsy/jsu037
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Association Between Sleep Disturbance in Children With Liver Transplants and Parent and Family Health-Related Quality of Life

Abstract: There are significant relationships between symptoms of SRBD and RLS/PLMS in children with liver transplants and family HRQOL. Behavior problems may account for these strong relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
1
7
0
1
Order By: Relevance
“…However, fatigue occurs in up to two‐thirds of adult patients with chronic cholestatic liver disease and biliary cirrhosis and persists even after LT . Considering that sleep quality is a known predictor of fatigue and sleep problems may contribute to fatigue, the results of three studies on sleep problems after PLT indicate that fatigue frequently occurs in PLT recipients. Furthermore, a recent review reported lower HRQL scores in PLT recipients with sleep disturbances …”
Section: Introductionmentioning
confidence: 99%
“…However, fatigue occurs in up to two‐thirds of adult patients with chronic cholestatic liver disease and biliary cirrhosis and persists even after LT . Considering that sleep quality is a known predictor of fatigue and sleep problems may contribute to fatigue, the results of three studies on sleep problems after PLT indicate that fatigue frequently occurs in PLT recipients. Furthermore, a recent review reported lower HRQL scores in PLT recipients with sleep disturbances …”
Section: Introductionmentioning
confidence: 99%
“…Es wurden entweder Instrumente zu Schlafstörungen eingesetzt oder nicht standardisiert nach Fatigue gefragt. In der Übersichtsarbeit von Parmar et al [17] identifizierten die Autoren bisher nur 3 Studien [34][35][36], die Schlafstörungen bei Kindern nach Lebertransplantation untersucht haben. Die Kinder, die an Schlafstörungen litten, wiesen eine niedrigere HRQoL auf.…”
Section: Fatigueunclassified
“…Similarly, weight management among teens provided greater benefit using family-focused approaches that used healthy diet and exercise (Santa Maria et al, 2014). Researchers concluded parents noted higher rates of sleep disturbances and periodic limb movement during sleep routines of adolescent with liver transplants (Andersen et al, 2014). Within the literature, a gap existed for specific parental strategies to promote and influence better sleep habits for adolescents.…”
Section: Parental Promotion and Influencementioning
confidence: 99%
“…Sleep health standards are relevant for restoration and healthy lifestyles including improved sports performance, academic achievement, and career success later in life (Zhu et al, 2013). Parental perceptions may prove significant to the adolescent health discipline, specifically for promoting healthy eating and physical activity at home (Andersen et al, 2014). (Moustakas, 1994).…”
Section: Research Design and Rationalementioning
confidence: 99%
See 1 more Smart Citation